Unemployment and Inflation in Nigeria - Nwevo Chimezie Nwikpo (Journal of Economics and Business Aseanomics, 2023)
Nigeria's economy is concerned by the rate of inflation and unemployment growth, which has become a recurrent decimal. Despite the government's best efforts, these macroeconomic problems have little to no impact on the economy. Consequently, this study looked at how unemployment in Nigeria affects inflation. The study's specific goals were to determine the impact of total government spending on inflation in Nigeria from 1981 to 2022 as well as the degree to which unemployment affects price increases in Nigeria. Unit root tests and ARDL tests served as the study's methodology. According to the empirical findings, unemployment had a negative long-term and short-term impact on inflation in Nigeria. Total government spending also had a positive long-term impact on inflation. The study suggests that in order to ensure an even and smooth operation of the economy, the government should make every effort to strike a balance between the unemployment rate and the inflation rate. In order to prevent a rise in inflation in the nation, the government should spend less and direct more of its resources toward the production sectors.